THE RELATIONSHIP BETWEEN STUDENTS' INTERNAL AND EXTERNAL FACTORS AND THEIR ACADEMIC ACHIEVEMENT - Siswantoro (Jurnal Penelitian Kebijakan Pendidikan, 2023)
This research aims to determine the relationship between students’ internal and external factors,  such as student background, school characteristics, teacher factors, and internet use and the  academic achievement of high school students majoring in science and social studies in Indonesia.  Employing a quantitative approach, the research utilizes panel data from all 34 provinces in  Indonesia over a span of 3 years, from 2017 to 2019. The data sources used are from the Ministry of  Education, Culture, Research, and Technology and the Central Bureau of Statistics. The data is  analyzed using random effect model through linear regression analysis of panel data. The results  show that student background factors, such as student participation and scholarship have a positive  and significant relationship with academic achievement. Additionally, school characteristic  factors, specifically, being a private school and the use of the Internet have been shown to have a  positive and significant relationship with academic achievement. However, the variables related to  teacher factors, specifically qualifications and certification do not have any significant relationship with students’ academic achievement.